Quote/Unquote Quotations on freedom of speech, journalism, the news media and a world or words - Rabe, Lizette (African Sun Media, 2016)
"Journalists live in a magical world of words - to inform, to educate, and to entertain ... to enlighten, to brighten, update, edify, amuse, tickle, distract and interest the likely and unlikely reader/listener/viewer/user. This collection consists of quotable and not so quotable quotes on journalists and the world of words, representing the art and craft and profession and fine calling of journalistic writing, from the prehistory of journalistic civilisation to the current everything-goes cyber universe."